1997
DOI: 10.1136/vr.140.11.282
|View full text |Cite
|
Sign up to set email alerts
|

Review of the literature and investigations on the prevalence and consequences of yeasts in reptiles

Abstract: Ninety-one reptiles were examined for the presence of yeasts by standard protocols and pathohistological methods. Yeasts were isolated from 42 of the animals. Representatives of herbivorous families (Testudinidae and Iguanidae) carried yeasts more often than animals belonging to carnivorous taxa (Boidae and Emydidae). Yeasts were most often isolated from the gastrointestinal tract, and in 24-6 per cent of cases they could be cultured from the oral cavity and/or cloaca of living animals. Postmortem examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 10 publications
(29 reference statements)
1
22
0
4
Order By: Relevance
“…Fungal infections in reptiles are considered more common in herbivore rather than carnivore reptiles (KOSTKA et al, 1997;MILDE et al, 2000). Under In conclusion, histological and molecular findings in this case confirmed the diagnosis of necrotizing and granulomatous pneumonia, tracheitis, arteritis, hepatitis, myocarditis, gastritis/enteritis, associated with Spencermartinsiella sp.…”
supporting
confidence: 58%
“…Fungal infections in reptiles are considered more common in herbivore rather than carnivore reptiles (KOSTKA et al, 1997;MILDE et al, 2000). Under In conclusion, histological and molecular findings in this case confirmed the diagnosis of necrotizing and granulomatous pneumonia, tracheitis, arteritis, hepatitis, myocarditis, gastritis/enteritis, associated with Spencermartinsiella sp.…”
supporting
confidence: 58%
“…In one of these cases, the authors demonstrated that high doses of R. mucilaginosa, but not of other fungi isolated from the skin of healthy or diseased chickens, reproduced the dermatitis under experimental conditions (Beemer et al, 1970). More recently, R. mucilaginosa has also been isolated from skin lesions in cetaceans (Shotts et al, 1990), and reptiles (Kostka et al, 1997). However, no reports have been previously published on the isolation of R. mucilaginosa from this kind of lesion in pinnipeds.…”
Section: Discussionmentioning
confidence: 93%
“…Fusarium spp., Microsporum spp., Mucor spp., Penicillium spp., and Rhodotolura spp. (Georg, et al, 1962, Jacobson, 1980a, Jacobson, et al, 1980b, Glazebrook and Campbell, 1990, Frye 1991, Glazebrook, et al, 1993, Gonzales, et al, 1995, Cabanes, et al, 1997, Kostka, et al, 1997, Posthaus, et al, 1997, H ernandez-D ivers, 2001, Rose, et al, 2001). However, Paecilomyces spp.…”
Section: Discussionmentioning
confidence: 99%